Dyeing waters: Does indiscriminate dye use threaten aquatic ecosystems? - Ross N. Cuthbert; Tatenda Dalu; Amanda Callaghan; Ellen J. Dolan; Barry Johnston (Science of The Total Environment, 2024)

Phenotypic plasticity as a cause and consequence of population dynamics - Dominic P. Brass; Christina A. Cobbold; David A. Ewing; Bethan V. Purse; Amanda Callaghan; Steven M. White (Ecology Letters, 2021)
Predicting complex species‐environment interactions is crucial for guiding conservation and mitigation strategies in a dynamically changing world. Phenotypic plasticity is a mechanism of trait variation that determines how individuals and populations adapt to changing and novel environments. For individuals, the effects of phenotypic plasticity can be quantified by measuring environment–trait relationships, but it is often difficult to predict how phenotypic plasticity affects populations. The assumption that environment–trait relationships validated for individuals indicate how populations respond to environmental change is commonly made without sufficient justification. Here we derive a novel general mathematical framework linking trait variation due to phenotypic plasticity to population dynamics. Applying the framework to the classical example of Nicholson's blowflies, we show how seemingly sensible predictions made from environment–trait relationships do not generalise to population responses. As a consequence, trait‐based analyses that do not incorporate population feedbacks risk mischaracterising the effect of environmental change on populations.

Assessing multiple predator, diurnal and search area effects on predatory impacts by ephemeral wetland specialist copepods - Ross N. Cuthbert; Tatenda Dalu; Ryan J. Wasserman; Cristián J. Monaco; Amanda Callaghan; Olaf L. F. Weyl; Jaimie T. A. Dick (Aquatic Ecology, 2020)
Predator–prey interaction strengths can be highly context-dependent. In particular, multiple predator effects (MPEs), variations in predator sex and physical habitat characteristics may affect prey consumption rates and thus the persistence of lower trophic groups. Ephemeral wetlands are transient ecosystems in which predatory copepods can be numerically dominant. We examine the interaction strengths of a specialist copepod Paradiaptomus lamellatus towards mosquito prey in the presence of conspecifics using a functional response approach. Further, we examine sex variability in predation rates of P. lamellatus under circadian and surface area variations. Then, we assess the influence of a co-occurring heterospecific predatory copepod, Lovenula raynerae , on total predation rates. We demonstrate MPEs on consumption, with antagonism between conspecific P. lamellatus predatory units evident, irrespective of prey density. Furthermore, we show differences between sexes in interaction strengths, with female P. lamellatus significantly more voracious than males, irrespective of time of day and experimental arena surface area. Predation rates by P. lamellatus were significantly lower than the heterospecific calanoid copepod L. raynerae , whilst heterospecific copepod groups exhibited the greatest predatory impact. Our results provide insights into the predation dynamics by specialist copepods, wherein species density, diversity and sex affect interaction strengths. In turn, this may influence population-level persistence of lower trophic groups under shifting copepod predator composition.

Sex demographics alter the effect of habitat structure on predation by a temporary pond specialist - Ross N. Cuthbert; Tatenda Dalu; Ryan J. Wasserman; Olaf L. F. Weyl; P. William Froneman; Amanda Callaghan; Jaimie T. A. Dick (Hydrobiologia, 2020)
Habitat structure can profoundly influence interaction strengths between predators and prey. Spatio-temporal habitat structure in temporary wetland ecosystems is particularly variable because of fluctuations in water levels and vegetation colonisation dynamics. Demographic characteristics within animal populations may also alter the influence of habitat structure on biotic interactions, but have remained untested. Here, we investigate the influence of vegetation habitat structure on the consumption of larval mosquito prey by the calanoid copepod Lovenula raynerae , a temporary pond specialist. Increased habitat complexity reduced predation, and gravid female copepods were generally more voracious than male copepods in simplified habitats. However, sexes were more similar as habitat complexity increased. Type II functional responses were exhibited by the copepods irrespective of habitat complexity and sex, owing to consistent high prey acquisition at low prey densities. Attack rates by copepods were relatively unaffected by the complexity gradient, whilst handling times lengthened under more complex environments in gravid female copepods. We demonstrate emergent effects of habitat complexity across species demographics, with predation by males more robust to differences in habitat complexity than females. For ecosystems such as temporary ponds where sex-skewed predator ratios develop, our laboratory findings suggest habitat complexity and sex demographics mediate prey risk.

Reproduction recovery of the crustacean Daphnia magna after chronic exposure to ibuprofen - Yuya Hayashi; Lars-Henrik Heckmann; Amanda Callaghan; Richard M. Sibly (Ecotoxicology, 2008)

A simple and rapid method for preserving RNA of aquatic invertebrates for ecotoxicogenomics - Lars-Henrik Heckmann; Anthony Bouetard; Christopher J. Hill; Richard M. Sibly; Amanda Callaghan (Ecotoxicology, 2007)

Haem Peroxidase Activity in Daphnia magna: A Biomarker for Sub-lethal Toxicity Assessments of Kerosene-contaminated Groundwater - Richard Connon; Rachel E. Dewhurst; Mark Crane; Amanda Callaghan (Ecotoxicology, 2003)